TRPA1 and substance P mediate stress induced duodenal lesions in water immersion restraint stress rat model - Xu, Yan; Huang, Caiqun; Deng, Hui; Jia, Ji; Wu, Youping; Yang, Jing; Tu, Weifeng (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Transient receptor potential ankyrin 1 (TRPA1) and substance P (SP), both expression in sensory neurons, have important roles in stress-induced duodenal lesions. The possible contribution of TRPA1 and SP to stress-induced duodenal lesions was explored by using the water immersion restraint stress (WIRS) rat model. Materials and Methods: Western blotting, Real-time polymerase chain reaction (RT-PCR), and immunohistochemistry assay were used to evaluate the changes of TRPA1and SP expression in the dorsal root ganglia (DRG, T8-11), the corresponding segment of the spinal cord (T8-11), and the duodenum in a duodenal lesions rat model. The SP concentrations of duodenal mucosa were investigated using an enzyme-linked immunosorbent assay (ELISA). Duodenal lesions were assessed according to histopathological changes. TRPA1 specific antagonist HC-030031 was intrathecally or intraperitoneally performed to suppress the expression of both TRPA1 and SP for evaluating the roles of TRPA1 and SP in duodenal lesions. Results: In contrast to the control group, TRPA1 and substance P in the DRG (T8-11) and duodenum were up-regulated, and concentrations of SP in the duodenal mucosa were increased after WIRS (p0.05). Conclusion: Our study indicates that TRPA1 antagonist HC-030031 alleviates duodenal lesions. TRPA1 is activated and sensitized, therefore concomitant neuropeptide SP is released, which exerts a critical role in inducing and maintaining duodenal lesions following WIRS in rats. This provides evidence that neuroimmune interactions may control duodenal injury. TRPA1 may be a potential drug target to inhibit the development of duodenal lesions by stress-induced in patients. Cite this article as: Xu Y, Huang C, Deng H, et al. TRPA1 and substance P mediate stress induced duodenal lesions in water immersion restraint stress rat model. Turk J Gastroenterol 2018; 29: 692-700.